PENERAPAN BUDAYA ORGANISASI PADA SEKOLAH TINGGI ILMU ADMINISTRASI (STIA) PANCA MARGA PALU - Pananrangi, Abdul Muin (Katalogis, 2013)
This study aims to determine the application of Organizational Culture on Private Higher School of Administration (STIA) Panca Marga Hammer City. Organizational culture is a common perception held by members of the organization, and is a sistem of shared meaning. According to Robbins to reveal the nature of the culture of an organization there are 7 (seven) dimensions that can be used in this study, among others, 1) Innovation and risk-taking, 2) Attention to detail, 3 ) outcome orientation, 4) People orientation, 5) Team orientation, 6) aggressiveness and 7) Stability. In this research, using qualitative methods of data analysis techniques used in the data processing Interactive Analysis Model. The informants in this study consists of various elements of the Element Leader, Academic Technical Implementation Elements, Elements Lecturer (Lecturer), Secretariat staff Elements, Elements and Elements Student Alumni. Selection of informants using purposive where informants selected based on their level of involvement and control the problem and research objectives.The results showed that the application of organizational culture in STIA Panca Marga Palu already applied. In its current state, an organization must have a value that can be used as a competitive advantage in the face of a very competitive especially in the realm of education. Related to the applied work attitude as it has been studied as one of the internalization of the values ​​and acculturation.